Analysis of electrogenesis' changes in mental retardation persons by using computer electroencephalography - B. Lobasyuk; L. Bartsevich; A. Zamkovaya (Kazimierz Wielki University, 2021)
Justification. Mental retardation is a persistent decrease in human cognitive activity against the background of organic damage to the central nervous system. Neurophysiological diagnostics, in particular electroencephalography (EEG), most adequately reflects the morpho-functional state of the central nervous system, which is the basis of the mechanisms of mental activity, and the originality of the bioelectrical activity of the brain can be considered as the main indicator that determines a decrease in the level of intellectual development and, thereby, characterizes this state. This provision actualizes the search for highly informative indicators of the originality of the bioelectrical activity of the brain in children with intellectual disabilities. Purspose. With the use of periodometric analysis investigate EEG's indicators and interhemispheric asymmetry of rhythms amplitudes in MR patients. Materials and methods. The EEG was recorded in a state of calm wakefulness with closed eyes with Neuron-Spectrum-2 electroencephalograph. Differences in indicators were tracked using the calculation of the coefficient of compliance (CC), EEG functional asymmetry coefficients in amplitude were determined, too. Results. It was revealed that in MR patients the amplitudes of the rhythms were greater than in healthy subjects. The greatest increase was determined in theta rhythm in the anterior temporal and posterior temporal leads in the left hemispheres. Duration indices in the delta, theta and alpha ranges of the EEG in mental retardation compared with the control group were increased, and the indices of the duration of beta rhythms - decreased. When analyzing FMPA in MR persons it turned out that in right-handers the negativeness of FMPA indices increased, and in left-handers there was an increase in the positivity of FMPA indices. Conclusions 1. With mental retardation, the amplitudes of the rhythms were greater than in healthy people. The greatest increase was determined in theta rhythm in the anterior temporal and posterior temporal leads in the left hemispheres. 2. The indices of duration in the delta, theta and alpha ranges of the EEG of MR subjects were increased, and the indices of the duration of beta rhythms - decreased. 3. When analyzing FMPA in MR persons, it turned out that in right-handers the negativeness of FMPA indices increased, and in left-handers there was an increase in the positivity of FMPA indices.